Unnoticed Professional Competence in Day Care Work - Ahrenkiel, Annegrethe; Schmidt, Camilla; Nielsen, Birger Steen; Sommer, Finn; Warring, Niels (Nordic Journal of Working Life Studies, 2013)
This article presents a double perspective on social educators’ professional competence: It discusses how everyday life in day care centres (preschools) is dependent on professional competences that can be conceived as “unnoticed.” These aspects of professional competence are embedded in routines, experiences and embodied forms of knowledge. However, it may be discussed whether these competences are under pressure from increased demands for documentation, standardization and evaluation of children’s learning outcomes. The article will briefly outline this development in the day care sector, followed by a discussion of unnoticed professional competence and the related notion of gestural knowledge. The double perspective on social educators’ professional competences will be illuminated by empirical examples from a research project involving social educators from two day care centres in Denmark.